"A Little Book of Logic" – Reconstructing Colonial Arts of Suasion at Government College, Umuahia. (21st February 2014) - Ochiagha, Terri
Abstract: Memories of political pedagogies in the elite colonial classroom are typically fragmentary and constitute limited historical evidence. But when contextualized and used in combination with coetaneous sources, such as textbooks and lesson notes, they can be crucial in the reconstruction of the transmission of political knowledge, its classroom assimilation and postcolonial negotiation. This article pieces together a number of unconnected but mutually consistent epiphanic moments in the life-writing and interviews of writers Chinua Achebe and Chike Momah, tracing and identifying a mysterious textbook of logic – R.W. Jepson's Clear Thinking (1936) – and its use as a tool to rein in and redirect anti-colonial nationalist undercurrents at Government College, Umuahia, the elite colonial school famous for having produced eight renowned Nigerian writers. Résumé: La mémoire des pédagogies politiques coloniales dans les écoles de l'élite sont généralement fragmentaires et ne représentent pas une preuve historique d'envergure. Cependant, mises en contexte et combinées avec des sources contemporaines, telles que les livres de texte et les notes des cours, elles peuvent se révéler cruciales dans la reconstruction de la transmission de la connaissance politique, de son assimilation en classe et de négociation postcoloniale. Cet article réunit différents moments épiphaniques sans interaction réciproque mais mutuellement cohérents de l'œuvre ("life-writing") et des interviews de Chinua Achebe et Chike Momah. Ainsi il trace et identifie un mystérieux manuel de logique, Clear Thinking de R.W. Jepson (1936 ), utilisé pour freiner et réorienter les courants nationalistes anticoloniaux sous-jacents au Government College, à Umuahia, l'école coloniale d'élite connue pour avoir produit huit célèbres écrivains nigérians.